Passion and language in the mechanics of political peace in Thomas Hobbes's Leviathan - Filho, Francisco Luciano Teixeira (Argumentos - Revista de Filosofia, 2015)
The paper deals with the political peace from mechanics of bodies in the Leviathan of Thomas Hobbes. It was sought to understand how a egoistic presumption can reach a consensus idea by language.